PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP RETURN SAHAM - ROSMIATI TARMIZI; HERRY GOENAWAN SOEDARSA; INDRAYENTI INDRAYENTI; DEASY ANDRIANTO (Universitas Bandar Lampung (UBL), 2018)
This study aims to determine the influence of liquidity ratio and profitability on stock return in the food and beverage companies that listed in Bursa efek Indonesia period 2014-2016. The type of this research is explanatory research with quantitative approach.Population in this research is food and beverages companies listed in Indonesia stock Exchange .Samples were collected by purposive sampling method amounted to 14 companies. The method of analysis used is multiple linear regression analysis method by using SPSS software version 18.The results of this study showed that current ratio and net profit margin negative effect on stock returns, while the quick ratio and return on equity has a positive effect on stock return.Keyword : Current Ratio (CR), Quick Ratio (QR), Net Profit Margin (NPM), Return On Equity (ROE), dan Return Saham.